Immunotherapy for gastrointestinal malignancies: the journey does not end here! - Almhanna, Khaldoun (Translational Gastroenterology and Hepatology, 2019)
Gastrointestinal malignancies represent a common and heterogeneous group of tumors and account for a high percentage of adult cancers. Over the past decades, early detection, advanced endoscopy and surgery, along with the additional benefit in some cases from perioperative treatment, have led to improved outcomes in localized disease. Disease recurrence and metastatic disease, as the primary presentation, are not uncommon and they carrie a very poor prognosis with median overall survival (OS) of less than 12 months from metastatic diagnosis with the exception of colon cancer where survival for stage IV disease is approaching 3 years.